2016
DOI: 10.3389/fmicb.2016.01489
|View full text |Cite
|
Sign up to set email alerts
|

Niche Filtering of Bacteria in Soil and Rock Habitats of the Colorado Plateau Desert, Utah, USA

Abstract: A common feature of microbial colonization in deserts is biological soil crusts (BSCs), and these comprise a complex community dominated by Cyanobacteria. Rock substrates, particularly sandstone, are also colonized by microbial communities. These are separated by bare sandy soil that also supports microbial colonization. Here we report a high-throughput sequencing study of BSC and cryptoendolith plus adjacent bare soil communities in the Colorado Plateau Desert, Utah, USA. Bare soils supported a community with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 59 publications
7
29
0
Order By: Relevance
“…The sequencing data affirm that Cyanobacteria is the dominant phylum in cryptoendolithic habitats (Hammes et al, 2013;Kurtz & Netoff, 2001;Kurtz et al, 2005;Lee et al, 2016). Previous studies have reported Chroococcidiopsis to be the predominant cyanobacteria observed in arid lithic systems based on morphological characterization (Bell, 1993;Bhatnagar & Bhatnagar, 2005;Büdel & Wessels, 1991;Casamatta et al, 2002;Friedmann, 1980;Pointing & Belnap, 2012;Wessels & Büdel, 1995).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The sequencing data affirm that Cyanobacteria is the dominant phylum in cryptoendolithic habitats (Hammes et al, 2013;Kurtz & Netoff, 2001;Kurtz et al, 2005;Lee et al, 2016). Previous studies have reported Chroococcidiopsis to be the predominant cyanobacteria observed in arid lithic systems based on morphological characterization (Bell, 1993;Bhatnagar & Bhatnagar, 2005;Büdel & Wessels, 1991;Casamatta et al, 2002;Friedmann, 1980;Pointing & Belnap, 2012;Wessels & Büdel, 1995).…”
Section: Discussionsupporting
confidence: 67%
“…In comparison with the community structure of local desert soils, we find that the overall structure is comparable, with Cyanobacteria and Proteobacteria numbers being higher on a relative basis (Garcia-Pichel, Johnson, Youngkin, & Belnap, 2003;Garcia-Pichel, Lopez-Cortes, & Nubel, 2001;Lee et al, 2016). However, we also note that while the structure is similar, the presence of certain phyla such as the Acidobacteria, Verrucomicrobia, and Planctomycetes is more pronounced in the soil environments (Gundlapally & Garcia-Pichel, 2006;Nagy, Pérez, & Garcia-Pichel, 2005).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…This partitioning at the OTU phylogenetic level was not recapitulated at higher taxonomic ranks suggesting differential adaptation of close relatives to the substrate's physical and chemical properties. Substrate‐dependent patterns of community structure have been reported for hypolithic quartz and endolithic sandstone communities from the Dry Valleys, Antarctica (Pointing et al ., ) and for sandstone communities from the Colorado Plateau, USA (Lee et al ., ). In all cases, while the hypolithic communities were recruited from the surrounding soils, habitat filtering shaped the assembly of the rock communities (Pointing et al ., ; Makhalanyane et al ., ; Lee et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…Substrate‐dependent patterns of community structure have been reported for hypolithic quartz and endolithic sandstone communities from the Dry Valleys, Antarctica (Pointing et al ., ) and for sandstone communities from the Colorado Plateau, USA (Lee et al ., ). In all cases, while the hypolithic communities were recruited from the surrounding soils, habitat filtering shaped the assembly of the rock communities (Pointing et al ., ; Makhalanyane et al ., ; Lee et al ., ). Community assembly controlled by the substrate was also observed for the hypolithic colonization of meteorites found in Nullarbor Plain, Australia (Tait et al ., ).…”
Section: Discussionmentioning
confidence: 97%